Best band ratio combinations for the lithological discrimination of the Dayang Bunting and Tuba Islands, Langkawi, Malaysia - Simon, Norbert; Che Aziz Ali,; Kamal Roslan Mohamed,; Kamilia Sharir, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Band ratio combination has been proven to be one of the most useful image processing methods for lithological discrimination, as discussed by many researchers in the past. In this study, bands from Landsat 5 TM were used to generate different ratio combinations to discriminate the different lithologies of two islands located at the southern end of the Langkawi archipelago, specifically the Dayang Bunting and Tuba Islands. Both islands comprise similar lithological units – namely, limestone/marble (Permian & Silurian-Ordovician), granite and alluvium. There are two rock formations that are limestone/marble dominated. The first is known as the Chuping Formation, which consists of limestone/marble and the other is the Setul Formation, which consists of not only limestone/marble but also of two detrital intervals. Different ratio combinations obtained from past researchers and that was produced from this study were tested on the image of the Dayang Bunting and Tuba Islands to identify the best ratio combinations that were able to discriminate the different lithologies for both islands. A total of 28 combinations were performed to examine which combinations are the most effective. From the 28 combinations, three were identified as the most suitable; 4/3 5/2 3/1, 5/3 4/3 4/1 and 4/2 5/3 4/3 in the RGB sequence. These combinations enhanced the spectral differences of each lithology unit so that it can be distinguished easily. Apart from the difference in the spectral response, the texture of the lithologies was also enhanced to assist in discriminating the different units.